Diet and colon: what matters?. Issue 2 (March 2019) - Pan, Pan; Yu, Jianhua; Wang, Li-Shu
Abstract : Purpose of review: Colorectal cancer (CRC) is one of the most common cancers and the fourth leading cause of cancer-related deaths worldwide. Diet has a significant impact on the risk of developing CRC, but though processed meat is a known positive contributor, the effects of other dietary components are largely mixed. This review focuses on dietary patterns to describe the complexity of dietary diversity and overall food consumption and to examine the relationship between dietary patterns and risk of CRC. Recent findings: After searching human studies published in 2017–2018, we selected and evaluated 30 articles, including meta-analyses, cohort studies, and prospective studies. These studies suggest that the prudent or Mediterranean dietary pattern significantly decreases the risk of CRC compared to the Western dietary pattern; a lower dietary inflammatory index or a higher dietary quality index associates with a lower risk of CRC; closely following all aspects of the World Cancer Research Fund/American Institute for Cancer Research cancer prevention guidelines and recommendations correlates with a reduced risk of CRC. Summary: The risk of developing CRC can be reduced by adopting a healthier lifestyle. More studies of the impact of diet on clinical outcomes of CRC are needed.